Lesiones orales más recurrentes en pacientes con prótesis removibles y totales: Revisión sistemática - Bello Yara, Evelyn Tatiana; Pastrana, María José; Carvajal, Nicole; Solano, Pedro (Universidad Antonio Nariño, 2023)
Introduction: The use of dental prostheses can originate different responses of the oral mucosa due to mechanical factors as well as chemical and even microbiological factors, which result in lesions which can appear and evolve both acutely and chronically. Objective: To carry out a systematic review to identify the most recurrent oral lesions in patients with removable and total partial dentures. Materials and methods: Systematic review study to identify the most frequent oral lesions in removable and total prostheses. Results: the most common lesions due to the use of prostheses correspond to prosthetic stomatitis and candidiasis. Conclusions: Aspects such as poor oral and appliance hygiene lead to the formation of microorganisms that lead to the appearance of oral lesions.